A Wireless Passive Sensing System for Displacement/Strain Measurement in Reinforced Concrete Members - Burak Ozbey; Vakur B. Erturk; Hilmi Volkan Demir; Ayhan Altintas; Ozgur Kurc (Sensors, 2016)
In this study, we show a wireless passive sensing system embedded in a reinforced concrete member successfully being employed for the measurement of relative displacement and strain in a simply supported beam experiment. The system utilizes electromagnetic coupling between the transceiver antenna located outside the beam, and the sensing probes placed on the reinforcing bar (rebar) surface inside the beam. The probes were designed in the form of a nested split-ring resonator, a metamaterial-based structure chosen for its compact size and high sensitivity/resolution, which is at µm/microstrains level. Experiments were performed in both the elastic and plastic deformation cases of steel rebars, and the sensing system was demonstrated to acquire telemetric data in both cases. The wireless measurement results from multiple probes are compared with the data obtained from the strain gages, and an excellent agreement is observed. A discrete time measurement where the system records data at different force levels is also shown. Practical issues regarding the placement of the sensors and accurate recording of data are discussed. The proposed sensing technology is demonstrated to be a good candidate for wireless structural health monitoring (SHM) of reinforced concrete members by its high sensitivity and wide dynamic range.